Correlation between the levels of non‐specific physical symptoms and pressure pain thresholds measured by algometry in patients with temporomandibular disorders. (8th October 2014) - Ramalho, D.; Macedo, L.; Goffredo Filho, G.; Goes, C.; Tesch, R.
Summary Recent studies showed that patients with chronic TMD pain also feature increased sensitivity in other craniofacial regions, and even in remote peripheral areas, suggesting that nociceptive processing is centrally facilitated in this patient population. The aim of this study was to investigate the existence of a negative correlation between the levels of non‐specific physical symptoms and pressure pain thresholds measured by algometry at sites distant from the chief complaint of oro‐facial pain in patients with TMD. A total of 20 female patients were evaluated comprising 11 patients diagnosed with myofascial pain (Group I of RDC/TMD) and 9 patients with arthralgia (Group III of RDC/TMD), with both reporting chronic TMD pain for at least 3 months. Patients were tested by the pressure algometry technique, and, in the same visit, clinical diagnosis and levels of non‐specific physical symptoms, including pain‐related issues or not, were obtained. The raw scores were then standardised into a T‐score. The possible correlation between the dependent variable levels of non‐specific physical symptoms and pressure pain thresholds measured by algometry at sites distant from the chief complaint of oro‐facial pain was assessed with Spearman's correlation coefficient. Results were considered statistically significant, which stood a lower than 5% probability of occurring by chance (P < 0·05). A statistically significant (P = 0·02) negative correlation (−0·51) was found to exist between the levels of non‐specific physical symptoms, only if including issues involving pain‐related symptoms, and experimental pressure pain thresholds in patients with painful TMD.